ZnO nanoparticles sensitized by CuInZnxS2+x quantum dots as highly efficient solar light driven photocatalysts - Donat, Florian; Corbel, Serge; Alem, Halima; Pontvianne, Steve; Balan, Lavinia; Medjahdi, Ghouti; Schneider, Raphaël (Beilstein Journal of Nanotechnology, 2017)
Alloyed CuInZnxS2+x (ZCIS) quantum dots (QDs) were successfully associated to ZnO nanoparticles by a thermal treatment at 400 °C for 15 min. The ZnO/ZCIS composite was characterized by TEM, SEM, XRD, XPS and UV–vis absorption spectroscopy. ZCIS QDs, with an average diameter of ≈4.5 nm, were found to be homogeneously distributed at the surface of ZnO nanoparticles. ZCIS-sensitized ZnO nanoparticles exhibit a high photocatalytic activity under simulated solar light irradiation for the degradation of Orange II dye (>95% degradation after 180 min of irradiation at an intensity of 5 mW/cm2). The heterojunction built between the ZnO nanoparticle and ZCIS QDs not only extends the light adsorption range by the photocatalyst but also acts to decrease electron/hole recombination. Interestingly, the ZnO/ZCIS composite was found to produce increased amounts of H2O2 and singlet oxygen 1O2 compared to ZnO, suggesting that these reactive oxygen species play a key role in the photodegradation mechanism. The activity of the ZnO/ZCIS composite is retained at over 90% of its original value after ten successive photocatalytic runs, indicating its high stability and its potential for practical photocatalytic applications.
Keywords: heterojunction; photocatalysis; quantum dots; reactive oxygen species; singlet oxygen; ZCIS quantum dots; ZnO

(untitled) - Hofmann, M. R.; Martin, S. T.; Choi, W. Y.; Bahnemann, D. W. (Chem. Rev., 1995)

(untitled) - Chen, X. B.; Mao, S. S. (Chem. Rev., 2007)

(untitled) - Moussa, H.; Girot, E.; Mozet, K.; Alem, H.; Medjahdi, G.; Schneider, R. (Appl. Catal., B: Environ., 2016)

(untitled) - Achouri, F.; Corbel, S.; Balan, L.; Mozet, K.; Girot, E.; Medjahdi, G.; Ben Said, M.; Ghrabi, A.; Schneider, R. (Mater. Des., 2016)

(untitled) - Chouchene, B.; Ben Chaabane, T.; Balan, L.; Girot, E.; Mozet, K.; Medjahdi, G.; Schneider, R. (Beilstein J. Nanotechnol., 2016)

(untitled) - Teets, T. S.; Nocera, D. G. (Chem. Commun., 2011)

(untitled) - Zhang, J.; Yu, J.; Jaroniec, M.; Gong, J. R. (Nano Lett., 2012)

(untitled) - Hisatomi, T.; Kubota, J.; Domen, K. (Chem. Soc. Rev., 2014)

(untitled) - Wang, H.; Zhang, L.; Chen, Z.; Hu, J.; Li, S.; Wang, Z.; Liu, J.; Wang, X. (Chem. Soc. Rev., 2014)

(untitled) - Yang, H.; Fan, W.; Vaneski, A.; Susha, A. S.; Teoh, W. Y.; Rogach, A. L. (Adv. Funct. Mater., 2012)

(untitled) - Labiadh, H.; Ben Chaabane, T.; Balan, L.; Becheik, N.; Corbel, S.; Medjahdi, G.; Schneider, R. (Appl. Catal., B: Environ., 2014)

(untitled) - Achouri, F.; Corbel, S.; Aboulaich, A.; Balan, L.; Ghrabi, A.; Ben Said, M.; Schneider, R. (J. Phys. Chem. Solids, 2014)

(untitled) - Robel, I.; Kuno, M.; Kamat, P. V. (J. Am. Chem. Soc., 2007)

(untitled) - Sun, W.-T.; Yu, Y.; Pan, H.-Y.; Gao, X.-F.; Chen, Q.; Peng, L.-M. (J. Am. Chem. Soc., 2008)

(untitled) - Yu, J. G.; Dai, G. P.; Huang, B. B. (J. Phys. Chem. C, 2009)

(untitled) - Li, G.-S.; Zhang, D.-Q.; Yu, J. C. (Environ. Sci. Technol., 2009)

(untitled) - Wang, X.; Liu, G.; Wang, L.; Chen, Z.-G.; Lu, G. Q.; Cheng, H.-M. (Adv. Energy Mater., 2012)

(untitled) - Yu, H.; Zhao, Y.; Zhou, C.; Shang, L.; Peng, Y.; Cao, Y.; Wu, L.-Z.; Tung, C.-H.; Zhang, T. (J. Mater. Chem. A, 2014)

(untitled) - Ratanatawanate, C.; Tao, Y.; Balkers, K. J., Jr (J. Phys. Chem. C, 2009)

(untitled) - Kolny-Olesiak, J.; Weller, H. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Zhang, W.; Zhong, X. (Inorg. Chem., 2011)

(untitled) - Michalska, M.; Aboulaich, A.; Medjahdi, G.; Mahiou, R.; Jurga, S.; Schneider, R. (J. Alloys Compd., 2015)

(untitled) - Michalska, M.; Florczak, A.; Dams-Kozlowska, H.; Gapinski, J.; Jurga, S.; Schneider, R. (Acta Biomater., 2016)

(untitled) - Kang, S.-Z.; Yang, Y.-K.; Bu, W.; Mu, J. (J. Solid State Chem., 2009)

(untitled) - Shen, F.; Que, W.; Liao, Y.; Yin, X. (Ind. Eng. Chem. Res., 2011)

(untitled) - Liu, R.; Liu, Y.; Liu, C.; Luo, S.; Teng, Y.; Yang, L.; Yang, R.; Cai, Q. (J. Alloys Compd., 2011)

(untitled) - Lin, Y.; Zhang, F.; Pan, D.; Li, H.; Lu, Y. (J. Mater. Chem., 2012)

(untitled) - Sun, J.; Zhao, J.; Masumoto, Y. (Appl. Phys. Lett., 2013)

(untitled) - Liu, X.; Tang, Y.; Luo, S.; Wang, Y.; Zhang, X.; Chen, Y.; Liu, C. (J. Photochem. Photobiol., A, 2013)

(untitled) - Li, T.; Li, X.; Zhao, Q.; Shi, Y.; Teng, W. (Appl. Catal., B: Environ., 2014)

(untitled) - Li, C.; Xi, Z.; Fang, W.; Xing, M.; Zhang, J. (J. Solid State Chem., 2015)

(untitled) - Asenjo, B.; Chaparro, A. M.; Gutiérrez, M. T.; Herrero, J.; Klaer, J. (Sol. Energy Mater. Sol. Cells, 2008)

(untitled) - Kuo, K.-T.; Liu, D.-M.; Chen, S.-Y.; Lin, C.-C. (J. Mater. Chem., 2009)

(untitled) - Shen, F.; Que, W.; He, Y.; Yuan, Y.; Yin, X.; Wang, G. (ACS Appl. Mater. Interfaces, 2012)

(untitled) - Li, Y.; Liu, Z.; Wang, Y.; Liu, Z.; Han, J.; Ya, J. (Int. J. Hydrogen Energy, 2012)

(untitled) - Scheunemann, D.; Wilken, S.; Parisi, J.; Borchert, H. (Appl. Phys. Lett., 2013)

(untitled) - Fakhri, H.; Mahjoub, A. R.; Chesme Khavar, A. H. (Appl. Surf. Sci., 2014)

(untitled) - Yu, Y.-X.; Ouyang, W.-X.; Liao, Z.-T.; Du, B.-B.; Zhang, W.-D. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Tang, Y.; Yun, J.-H.; Wang, L.; Amal, R.; Ng, Y. H. (Dalton Trans., 2015)

(untitled) - Scheunemann, D.; Wilken, S.; Parisi, J.; Borchert, H. (ACS Photonics, 2015)

(untitled) - Scheunemann, D.; Wilken, S.; Parisi, J.; Borchert, H. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Moussa, H.; Merlin, C.; Dezanet, C.; Balan, L.; Medjahdi, G.; Ben-Attia, M.; Schneider, R. (J. Hazard. Mater., 2016)

(untitled) - Chuang, P.-H.; Lin, C. C.; Liu, R.-S. (ACS Appl. Mater. Interfaces, 2014)

(untitled) - Xu, Y.; Schoonen, M. A. A. (Am. Mineral., 2000)

(untitled) - Long, M. C.; Cai, W. M.; Cai, J.; Zhou, B. X.; Chai, X. Y.; Wu, Y. H. (J. Phys. Chem. B, 2006)

(untitled) - Zhu, X.; Castleberry, S. R.; Nanny, M. A.; Butler, E. C. (Environ. Sci. Technol., 2005)

(untitled) - Rincón, A.-G.; Pulgarin, C. (Appl. Catal., B: Environ., 2004)

(untitled) - Chen, H. Y.; Zahraa, O.; Bouchy, M. (J. Photochem. Photobiol., A: Chem., 1997)

(untitled) - Litter, M. I. (Appl. Catal., B: Environ., 1999)

(untitled) - Nosaka, Y.; Daimon, T.; Nosaka, A. Y.; Murakami, Y. (Phys. Chem. Chem. Phys., 2004)

(untitled) - Jańczyk, A.; Krakowska, E.; Stochel, G.; Macyk, W. (J. Am. Chem. Soc., 2006)

(untitled) - Daimon, T.; Nosaka, Y. (J. Phys. Chem. C, 2007)

(untitled) - Daimon, T.; Hirakawa, T.; Kitazawa, M.; Suetake, J.; Nosaka, Y. (Appl. Catal., A, 2008)

(untitled) - Rengifo-Herrera, J. A.; Pierzchala, K.; Sienkiewicz, A.; Forró, L.; Kiwi, J.; Pulgarin, C. (Appl. Catal., B: Environ., 2009)

(untitled) - Zhang, D.; Qiu, R.; Song, L.; Eric, B.; Mo, Y.; Huang, X. (J. Hazard. Mater., 2009)

(untitled) - Flors, C.; Fryer, M. J.; Waring, J.; Reeder, B.; Bechtold, U.; Mullineaux, P. M.; Nonell, S.; Wilson, M. T.; Baker, N. R. (J. Exp. Bot., 2006)

(untitled) - Gollmer, A.; Arnbjerg, J.; Blaikie, F. H.; Pedersen, B. W.; Breitenbach, T.; Daasberg, K.; Glasius, M.; Ogilby, P. R. (Photochem. Photobiol., 2011)

(untitled) - Redmond, R. W.; Gamlin, J. N. (Photochem. Photobiol., 1999)

(untitled) - Bancirova, M. (Luminescence, 2011)

(untitled) - Miskoski, S.; García, N. A. (Photochem. Photobiol., 1993)

(untitled) - Telfer, A.; Bishop, S. M.; Phillips, D.; Barber, J. (J. Biol. Chem., 1994)

(untitled) - Ishibashi, K.-i.; Nosaka, Y.; Hashimoto, K.; Fujishima, A. (J. Phys. Chem. B, 1998)

(untitled) - Naito, K.; Tachikawa, T.; Fujitsuka, M.; Majima, T. (J. Phys. Chem. C, 2008)